Dosimetric effects of a repositioning head frame system and treatment planning system dose calculation accuracy. (25th September 2018) - Ferrer, Carlos; Huertas, Concepción; Plaza, Rodrigo; Aza, Zulima; Corredoira, Eva
Abstract: This work aims to study the effect on surface dose and dose distribution caused by the Elekta Fraxion cranial immobilization system. The effect of Fraxion inclusion in Elekta Monaco treatment planning system and its calculation accuracy is also checked. To study the dose attenuation, a cylindrical phantom was located over the Elekta Fraxion with an IBA CC13 ionization chamber placed in the central insert at the linac isocenter. Dose measurements at multiple gantry angles were performed for three open fields, 10 × 10 cm, 5 × 5 cm and other smaller 2 × 2 cm. Measured doses were compared with the ones calculated by Monaco. Surface dose and dose distribution in the buildup region were measured placing several Gafchromic Films EBT3 at linac CAX between the slabs of a RW3 phantom located over Fraxion and read using FilmQA Pro software. Measures were performed for two open field sizes and results were compared with Monaco calculations. Measurements show a 1% attenuation for 180° gantry angle but it can be as high as 3.4% (5 × 5 open field) for 150°/210° gantry angle, as with these angles the beam goes through the Fraxion's headrest twice. If Fraxion is not included in the calculation Monaco calculation can result in a 3% difference between measured and calculated doses, while with Fraxion in the calculation, the maximum difference is 0.9%. Fraxion increases 3.7 times the surface dose, which can be calculated by Monaco with a difference lower than 2%. Monaco also calculated correctly the PDD for both open fields (2%) when Fraxion is included in the calculation. This work shows that the attenuation varies with gantry angle. The inclusion of Fraxion in Monaco improves the calculation from 3% difference to 1% in the worst case. Furthermore, the surface dose increment and the dose in the buildup region are correctly calculated.